Getting started with Kubernetes : orchestrate and manage large-scale Docker deployments with Kubernetes to unlock greater control over your infrastructure and extend your containerization strategy /: orchestrate and manage large-scale Docker deployments with Kubernetes to unlock greater control over your infrastructure and extend your containerization strategy. (2015) - Baier, Jonathan
No abstract available